(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This study explores the field of phraseology, focusing on fixed expressions such as idioms, collocations, proverbs, and phrasal verbs that play a vital role in language structure and communication. It examines the theoretical foundations of phraseology, the classification of phraseological units, and their significance in linguistic studies. The research highlights the cultural and semantic complexities of these expressions, emphasizing their importance in language teaching, translation, and lexicography. Additionally, it addresses the challenges posed by phraseological analysis, including cultural specificity and semantic opacity. The paper concludes with an overview of how the evolving nature of language, influenced by digital communication, shapes modern phraseology. This research contributes to a deeper understanding of language’s richness and the role of fixed expressions in effective communication.